Mechanisms of Injury Among the Amish Population in Central Pennsylvania. Issue 4 (April 2022) - Whitney, Larissa; Bonneville, Kelly; Morgan, Madison; Perea, Lindsey L.
Background: Individuals presenting with traumatic injury in rural populations have significantly different injury patterns than those in urban environments. With an increasing Amish population, totaling over 33 000 in our catchment area, their unique way of life poses additional factors for injury. This study aims to evaluate differences in mechanism of injury, location of injury, and demographic patterns within the Amish population. We hypothesize that there will be an increased incidence of agriculture-related mechanisms of injury. Methods: All Amish trauma patients presenting to our level I trauma center over 20 years (1/2000-4/2020) were retrospectively analyzed. Mechanism and geographic location of injury were collected. Demographic and clinical variables were compared between the age groups. Results: There were 1740 patients included in the study with 36.4% (n = 634) ≤ 14 years. Only 10% (n = 174) were ≥ 65 years. The most common mechanism across all ages was falls. However, when separating out the pediatric population ( ≤ 14 years), 27.8% (n = 60) fell from a height on average > 8-10 feet. The most common geographic location of injury was at home in all age groups, except for the 15-24 year group, which was roadways. Discussion: The Amish population poses a unique set of mechanisms of injury and thus injury patterns to rural trauma centers. We have found the most common injuries to be falls, buggy accidents, animal-related injuries, and farming accidents across all age groups. Future research and collaboration with other rural trauma centers treating large Amish populations would be beneficial to maximize injury prevention in this population. Level of Evidence: Level 3a, epidemiological.